'The exception to the rule': exploring the exception and the exceptional in planning policy. Issue 5 (1st September 2021) - Harris, Neil
Abstract : This article explores exceptions to planning 'rules' as a specific form of discretion exercised by planners and decision makers. Theoretical and conceptual ideas on rules and exceptions to rules, drawing principally on administrative and political decision making, are used to examine the role of exceptions and exceptional circumstances in planning. This analysis addresses the interdependency between exceptions and 'rules', the circumstances in which planning decision makers are invited to consider exceptions to rules or exceptional circumstances, and the distinct forms of planning regulation created using exceptions. The conclusions call for systematic analysis of the role that exceptions play in different contexts and planning systems.